Tarpkonfesinė sąveika ir tikybinio identiteto paieškos Lietuvos Didžiojoje Kunigaikštystėje XVI a. pab. – XVII a. I pusėje: akcentai Rapolo Korsako „Juozapo Benjamino Rutskio gyvenime“ (1640) - Čiurinskas, Mintautas (Literatūra, 2015)
This article focuses on the biography of the metropolitan of the Ruthenian Uniats Joseph Velamin Rutski, written in Latin by his successor Raphael Korsak. This interesting biographical work remained unfinished and unpublished till 20th century. Not only detailed analysis of this work is presented in the article, the biography is also taken as the source and the basis for some broader conclusions in the field of formation of the religious identity in the Grand Duchy of Lithuania, mainly in the first part of the 17th century. Such approach is allowed by several circumstances related with this work – close personal relation between the described person and the author, the similarity of their biographies. The high education and ecclesiastical position of the author allowed to make many important remarks about the described times. The accuracy representing details and attention to the life of the spirit of the described person (which were elements taken from the tradition of Jesuit biography) preserved very much authentic material from the early history of the Uniat Church and vividly reveal difficulties in the life of the citizen of GDL in the way toward Uniat Church and Eastern-Rite Catholicism as one’s own religious identity. On the basis of this work and also of some other biographical and historical writings related with Uniat Church we can distinguish some events as common sites of memory, which became significant signs for this identity (an attempt on the life of the metropolitan of uniats in Vilnius, the martyrdom of archbishop of Pollock Jozafat Kuncewicz and the conversion of Meletius Smotrycki, which took place afterwards).